2023
DOI: 10.1128/spectrum.03861-22
|View full text |Cite
|
Sign up to set email alerts
|

Palmitoyl Transferase FonPAT2-Catalyzed Palmitoylation of the FonAP-2 Complex Is Essential for Growth, Development, Stress Response, and Virulence in Fusarium oxysporum f. sp. niveum

Abstract: Fusarium oxysporum f. sp. niveum ( Fon ), the causal agent of watermelon Fusarium wilt, is one of the most serious threats for the sustainable development of the watermelon industry worldwide. However, little is known about the underlying molecular mechanism of pathogenicity in Fon .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 76 publications
2
4
0
Order By: Relevance
“…Thus, FonKin4 likely influences Fon pathogenicity by regulating its invasive growth within host plants, consistent with the observed deficiencies in vegetative growth and asexual reproduction ( Figure 4 ). This mechanism parallels findings for FonPUF1, FonNST2, and FonPAT2 in Fon pathogenicity ( Gao et al, 2022 , 2023 ; Xiong et al, 2023 ). Furthermore, FonKin4 participated in stress responses against multiple cell wall-perturbing agents and oxidative stress-inducing factors ( Figure 5 ).…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Thus, FonKin4 likely influences Fon pathogenicity by regulating its invasive growth within host plants, consistent with the observed deficiencies in vegetative growth and asexual reproduction ( Figure 4 ). This mechanism parallels findings for FonPUF1, FonNST2, and FonPAT2 in Fon pathogenicity ( Gao et al, 2022 , 2023 ; Xiong et al, 2023 ). Furthermore, FonKin4 participated in stress responses against multiple cell wall-perturbing agents and oxidative stress-inducing factors ( Figure 5 ).…”
Section: Discussionsupporting
confidence: 86%
“…This reduction in pathogenicity in the ΔFonPARP1 mutant primarily stemmed from a defect in invasive growth within watermelon plants ( Figures 1D – G ) rather than an impairment in its ability to penetrate the host ( Supplementary Figure S6 ). This pattern mirrors the functions of previously identified pathogenicity factors, including FonNst2, FonPAT2, and FonPUF1, whose deletion mutants exhibited reduced pathogenicity due to compromised in planta invasive growth and colonization within host plants ( Gao et al, 2022 , 2023 ; Xiong et al, 2023 ). Our study also revealed that FonPARP1 undergoes self-PARylation in vitro ( Figure 7A ), indicating its active PARP activity in Fon .…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Palmitoyl transferase FonPAT2 regulates the growth, development, stress response and virulence of F. oxysporum f. sp. niveum by palmitoylation of the FonAP‐2 Complex (Xiong et al., 2023 ).…”
Section: Identification and Pathogenicity Of Root Rot Pathogens In ...mentioning
confidence: 99%
“…Directed mutation of pat1, pat2 and pat4 showed that their palmitoyl transferase activity is dependent upon the presence of a cysteine residue in the DHHC motif. These three palmitoyl transferases have clear effects on growth, formation of asexual spores and conidia morphology, in addition to the response to the cell wall and metal ions stressing factors [135]. An important observation was the fact that the lack of Pat1, Pat2 or Pat4 reduces fungal virulence in plants probably by alteration of the formation of toxic metabolites [106,136].…”
Section: Protein Palmitoylation In Plant Pathogenic Fungi: the Cargo ...mentioning
confidence: 99%